Experimental study on modal analysis and vibration response of tunnel structures under different damage conditions due to subway train loads - Rui Hou; Tao Li; Zhongyu Zhang; Lingfeng Li; Bo Liu; Dongwei Ren (Scientific Reports)
Abstract Based on a prototype of the Beijing subway tunnel, this research conducts large-scale model experiments to systematically investigate the vibration response patterns of tunnels with different damage levels under the influence of measured train loads. Initially, the polynomial fitting modal identification method (Levy) and the model test preparation process are introduced. Then, using time-domain peak acceleration, frequency response function, frequency-domain modal frequency, and modal shape indicators, a detailed analysis of the tunnel’s dynamic response is conducted. The results indicate that damage significantly amplifies vibration acceleration, with the amplification increasing with the severity of the damage. When the crack lengths are 2 cm, 4 cm, and 6 cm, the peak acceleration increases by 25.12%, 36.35%, and 50.29%, respectively, while adjacent segments show increases of 13%, 29%, and 45%. Damage decreases the tunnel structure’s modal frequency, with the first two modal frequencies showing the most significant reductions of 9.87% and 7.34%, respectively. The adjacent segments show reductions of 7.7% and 4.2%. As the severity of the damage increases, the amplitude of the modal shape at the damaged location also increases, with the first modal shape rising by 43.37% for 4 cm damage compared to 2 cm damage and by 72.21% for 6 cm damage. The second modal shape increases by 9.04% and 26.51%, respectively. Additionally, the effectiveness of the polynomial fitting modal identification method (Levy) for tunnel structural damage detection was validated. Finally, based on the methods outlined above, the tunnel responses measured on-site in the Beijing metro were also analyzed. The findings of this study provide important theoretical support for the assessment and routine maintenance of metro tunnels.